2016
DOI: 10.3126/jnps.v36i2.15605
|View full text |Cite
|
Sign up to set email alerts
|

Reference Ranges for Hematological Values in Umbilical Cord Blood in Pokhara, Nepal

Abstract: Introduction: Reference hematological values in newborns

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
8
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 5 publications
8
8
4
Order By: Relevance
“…The Hgb values (13.3-19.6 g/dl) of this study almost agrees with a study reported in Saudi Arabia (15.7-19.7 g/ dl), however, the upper limit of platelet value (413 × 10 9 /l) the present study was greater than as compared to the upper limit of Saudi reported (297 × 10 9 /l) [20]. On the other hand, Our finding of the 95% RI of RBC (3.69-5.47) values was comparable to a study reported in Nepal (3.67-4.93) [21], Iran (3.61-5.29) [22], and Nigeria (3.52-4.62) [23] reported. Similarly, the 95% RI of WBC (7.64-22.16 × 10 9 /l) in our study similar to the study conducted in Turkey (71.90-25.44 × 10 9 /l) [24].…”
Section: Discussioncontrasting
confidence: 58%
“…The Hgb values (13.3-19.6 g/dl) of this study almost agrees with a study reported in Saudi Arabia (15.7-19.7 g/ dl), however, the upper limit of platelet value (413 × 10 9 /l) the present study was greater than as compared to the upper limit of Saudi reported (297 × 10 9 /l) [20]. On the other hand, Our finding of the 95% RI of RBC (3.69-5.47) values was comparable to a study reported in Nepal (3.67-4.93) [21], Iran (3.61-5.29) [22], and Nigeria (3.52-4.62) [23] reported. Similarly, the 95% RI of WBC (7.64-22.16 × 10 9 /l) in our study similar to the study conducted in Turkey (71.90-25.44 × 10 9 /l) [24].…”
Section: Discussioncontrasting
confidence: 58%
“…x10 9 /l) (23) and Sagamu Nigeria (4.3 x10 9 /l). On the contrarily, the higher limit of RI of Hgb value (19.6g/dl) of this study was consistent to a study reported in Saudi Arabia (19.7g/dl) (23) but higher than in a study reported in Logas Nigeria (14.8g/dl) (17), Pakistan (17.3g/dl) (25), Iraq (15.22g/dl) (26), and Nepal (17.2g/dl) (18). The difference of Hgb value might be due to method variation, inclusion criteria of the study participants and time of cord clamping.…”
Section: Discussionsupporting
confidence: 92%
“…The of Hgb values (13.3-19.6g/dl) of this study almost agrees with a study reported in Saudi Arabia (15.7-19.7g/dl), however, the upper limit 97.5 th percentiles of platelet value (413 x10 9 /l) the present study was greater than as compared to the upper limit of Saudi reported (297 x10 9 /l) (23). On the other hand, Our nding of the 95% RI of RBC (3.69-5.47) values were comparable to a study reported in Nepal (3.67-4.93) (18), Iran (3.61-5.29) (19), and Nigeria (3.52-4.62) (20) reported. Similarly, the 95% RI of WBC (7.64-22.16 x10 9 /l) in our study similar to the study conducted in Turkey ( 71.90-25.44 x10 9 /l) (24).…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations